Iterative breakthrough invasive aspergillosis due to TR(34)/L98H azole‐resistant Aspergillus fumigatus and Emericella sublata in a single hematopoietic stem cell transplant patient. Issue 4 (10th May 2014) - de Fontbrune, F.S.; Denis, B.; Meunier, M.; Garcia‐Hermoso, D.; Bretagne, S.; Alanio, A.
Abstract We report 3 consecutive episodes of invasive aspergillosis in a single hematopoietic stem cell transplant patient successively attributed to TR(34)/L98H azole‐resistant Aspergillus fumigatus and to a first occurrence of invasive Emericella sublata infection. This case illustrates potential selection of resistant molds during antifungal therapy in hematological patient.